Haemodynamic Effects and Complications of Unilateral Spinal versus Standard Spinal Anesthesia in Elderly with Low Ejection Fraction Undergone Lower-Limb Surgery (Delta Medical College Journal, 2017)
Background: Cardiovascular system may be profoundly affected by spinal anaesthesia due to unavoidable sympathetic blockade which is more prominent in elderly.A restricted sympathetic block during spinal anesthesia may minimize hemodynamic changes.Objective: To assess whether a unilateral spinal anaesthesia using 0.5% hyperbaric bupivacaine will restrict the sympathetic block to avoid the undesired cardio vascular effects.Materials and method: In this prospective study 60 ASA Ill and IV patients aged between 60-90 years undergoing unilateral lower limb surgery were included. Patients were divided into two groups. In group-A, dural puncture was performed with the patient in the lateral decubitus position with 1.5 mL of hyperbaric bupivacaine. In group-B, it was performed with the patient in a seated position using 1.5 mL hyperbaric bupivacaine. Each patient was then placed in supine position. The speed of injection was 1 mL/30s. Patients were placed in the lateral position with operated side down and kept in this position for 10 minutes. Motor and sensory levels were assessed, and haemodynamic alterations were monitored just after block, 5, 10, 15 and 30 minutes of spinal anaesthesia.Results: The demographic data were found similar in both groups. The time to the onset of the sensory and motor block was significantly shorter in group-B. The duration of motor and sensory block was significantly shorter in group-A. Haemodynamically all the parameters revealed better out come in unilateral spinal anesthesia. The incidence of complications (nausea, headache, and hypotension) was also lower in group A.Conclusion: When unilateral spinal anesthesia was performed using a low-dose, low-volume and low-flow injection technique, it provides adequate sensory-motor block and helps to achieve stable hemodynamic parameters during surgery on a lower limb. Furthermore, this technique avoids unnecessary paralysis on the non-operated side.Delta Med Col J. Jan 2017 5(1): 20-24